Correlation between level of autophagy and frequency of CD8+ T cells in patients with chronic obstructive pulmonary disease. Issue 9 (September 2020) - Zhuang, Hong; Li, Na; Chen, Sida; Shen, Yan; Zhan, Wugen; Xu, Xiangqun; Zhuo, Songming
Objective: The pathogenesis of chronic obstructive pulmonary disease (COPD) remains elusive. Here, we assessed the correlation between CD8 + T cell frequencies and autophagy in COPD patients. Methods: Subjects were divided into three groups (n = 30 patients/group): (1) COPD patients in the stable phase; (2) smokers with normal lung function; and (3) non-smokers with normal lung function. Flow cytometry was used to enumerate CD8+ T cell subsets (CD8 +, CD8 + effector, and CD8 + memory T cells) and quantitate T-cell apoptosis. RT-PCR and western blotting were used to measure levels of LC3 and p62. Results: Frequencies of CD8 + T cell subsets and expression of p62 and LC3 II/I were significantly higher in COPD patients compared with the other two groups, while the rate of apoptosis was lower. In COPD patients, LC3 II/I and p62 expression were positively correlated with CD8 + T cell subset frequencies. Moreover, a significant correlation was observed between LC3 II/I and p62 expression and T cell subset frequencies. Conclusion: Autophagy level is positively correlated with the frequencies of CD8 + T cells, suggesting that autophagy might be involved in COPD pathogenesis.